High-mobility group box1 as an amplifier of immune response and target for treatment in Aspergillus fumigatus keratitis - Wu, Meng-Qi (Int J Ophthalmol, 2020)
AIM: To determine the roles of high-mobility group box1 (HMGB1) in pro-inflammation, host immune response and its potential target for treatment in Aspergillus fumigatus (A.fumigatus) keratitis. METHODS: Expression of HMGB1 was tested in C57BL/6 normal and infected corneas. Dual immunostaining tested co-expression of HMGB1 with TLR4 or LOX-1. C57BL/6 mice were pretreated with Box A or PBS and then infected. Clinical scores, polymerase chain reaction, ELISA, and MPO assay were used to assess the disease response. Flow cytometry were used to test the effect of Box A on reactive oxygen species (ROS) expression after A.fumigatus stimulation in polymorphonuclear neutrophilic leukocytes (PMN). C57BL/6 peritoneal macrophages were pretreated with Box B before A.fumigatus stimulation, and MIP-2, IL-1β, TNF-α, HMGB1 and LOX-1 were measured. Macrophages were pretreated with Box B or Box B combined with Poly(I) (an inhibitor of LOX-1) before stimulating with A.fumigatus, and MIP-2, IL-1β, TNF-α, LOX-1, p38-MAPK, p-p38-MAPK were measured. RESULTS: HMGB1 levels were elevated in C57BL/6 mice after infection. HMGB1 co-expressed with TLR4, and LOX-1 in infiltrated cells. Box A vs PBS treated C57BL/6 mice had lower clinical scores and down-regulated corneal HMGB1, MIP-2, IL-1β expression and neutrophil influx. Box B treatment amplified expression of MIP-2, IL-1β, TNF-α, HMGB1 and LOX-1 that induced by A.fumigatus in macrophage. Compared to the treatment of Box B only, the protein expression of IL-1β, TNF-α showed inhibition of Box B combined with Poly(I), which also reduced the A.fumigatus-evoked protein level of LOX-1 and phosphorylation level of p38-MAPK. The production of A.fumigatus-stimulated ROS was significantly declined after Box A pretreatment in PMN. CONCLUSION: Blocking HMGB1 reduces the disease response in C57BL/6 mice. HMGB1 can amplify the host immune response through p38-MAPK, and is a target for treatment of A.fumigatus keratitis.